Caron praises VBC; is at risk for 90 days post‐discharge. Issue 19 (14th May 2021) - Knopf, Alison
Abstract : Signing an agreement with a managed care company may not seem like a path to profit and good patient care, but for the legendary Caron, it has been working out. Value‐based contracting (VBC) is what it sounds like: giving the insurance company value for its money. But this is not based on limiting days or type of treatment, just dollars. And as long as those dollars are agreed upon, all is well, according to Joseph Garbely, D.O., chief medical officer at Caron, in an interview with ADAW .